2008
DOI: 10.2223/jped.1773
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal from glucocorticosteroid therapy: clinical practice recommendations

Abstract: ResumoObjetivo: Apresentar uma revisão atualizada e prática sobre como efetuar de forma segura a retirada da corticoterapia. Fontes dos dados:Revisão da literatura utilizando os bancos de dados MEDLINE e LILACS (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), selecionando os artigos mais atuais e representativos do tema. Síntese dos dados:Três situações clínicas podem ocorrer durante a retirada da corticoterapia prolongada: insuficiência adrenal secundária à supressão do eixo hipotálamo-hipó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 43 publications
1
35
0
12
Order By: Relevance
“…Further, in clinical aspect, it is a cause of death with extremely high mortality rates in patients undergoing major surgery [28]. Although glucocorticosteroids remain the most effective therapy for inflammatory disorders, the side effects limit their clinical usefulness [29]. High-dose of corticosteroids to treat sepsis has been one of controversial clinical issues [30], and administration of high-dose corticosteroids does not benefit to treat patients with early and severe sepsis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in clinical aspect, it is a cause of death with extremely high mortality rates in patients undergoing major surgery [28]. Although glucocorticosteroids remain the most effective therapy for inflammatory disorders, the side effects limit their clinical usefulness [29]. High-dose of corticosteroids to treat sepsis has been one of controversial clinical issues [30], and administration of high-dose corticosteroids does not benefit to treat patients with early and severe sepsis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct stenosis in the distal third part was significantly improved after 2 weeks in each group Although oral prednisolone was commenced, it had had no effect on the biliary stenosis (left). Two courses of steroid pulse therapy ameliorated the stenosis dramatically (right) (Case 10; reference [31]) secondary adrenal insufficiency due to hypothalamicpituitary-adrenal suppression [21][22][23]. Diagnostic treatment with an oral steroid may cause an undesirable effect when surgical resection is required.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Korean investigators have reported the usefulness of a 2 weeks' trial of oral steroids in differentiating AIP from malignancy, with continuing administration if AIP is diagnosed [20]. However, it has not yet been established whether or not withdrawal of steroids in reconsidering malignancy presents a risk of postoperative adrenal insufficiency [21][22][23]. Therefore, it is desirable to have an alternative to the discontinuation of steroid administration immediately after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the risk of onset of symptoms related to GC deprivation [27], a 6-month tapering (reduction of 10 % of the dose each week) regimen was planned. When an alternate daily 5-2.5 mg dosage of prednisone was reached, it was maintained for 3 weeks to minimize the risk of deprivation syndrome consequent to subphysiological GC dosages [28]. Patients with any complaints were examined within 1 week; others were re-examined 6 months after enrollment (T6).…”
Section: Gc Tapering Regimen and Follow-up Visitsmentioning
confidence: 99%